2022
DOI: 10.1152/ajpregu.00086.2022
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine innervation of the supraoptic nucleus contributes to increased copeptin and dilutional hyponatremia in male rats

Abstract: Dilutional hyponatremia associated with liver cirrhosis is due to inappropriate release of arginine vasopressin (AVP). Elevated plasma AVP causes water retention resulting in a decrease in plasma osmolality. Cirrhosis, in this study caused by ligation of the common bile duct (BDL), leads to a decrease in central vascular blood volume and hypotension, stimuli for non-osmotic AVP release. The A1/A2 neurons stimulate the release of AVP from the supraoptic nucleus (SON) in response to non-osmotic stimuli. We hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 82 publications
3
5
0
Order By: Relevance
“…Our results show that liver cirrhosis was successfully induced in the BDL rats due to their relatively higher liver weight to bodyweight ratio as compared to the sham rats. This was consistent with our previous studies 17,18,39,41 . Also, plasma osmolality and hematocrit values in the BDL rats were significantly lower than those from sham rats.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results show that liver cirrhosis was successfully induced in the BDL rats due to their relatively higher liver weight to bodyweight ratio as compared to the sham rats. This was consistent with our previous studies 17,18,39,41 . Also, plasma osmolality and hematocrit values in the BDL rats were significantly lower than those from sham rats.…”
Section: Discussionsupporting
confidence: 93%
“…[15][16][17] A recent publication from our laboratory has suggested that the increased plasma AVP concentration associated with these disorders could be caused in part by increased stimulation of SON AVP neurons by noradrenergic A1 and A2 neurons due to a decreased central blood volume. 18 This is consistent with the traditional view that inappropriate AVP release in cirrhosis is due to a change in non-osmotic regulatory pathways. 19 However, since patients with liver failure are hypoosmotic, a stimulus that inhibits the release of AVP, it suggests a possible failure of inhibitory mechanisms could play a role in the increased plasma AVP and dilutional hyponatremia observed.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations